2017
DOI: 10.1051/bioconf/20170903008
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian sparkling wine: A successful trajectory

Abstract: The objective of this study was to explore the evolution of internal and external commercialization of Brazilian sparkling wines during the period between 1986 and 2015, giving an overview of the current situation and its market trends, and highlighting the importance of Brazil in the world scenario for sparkling wines. This research is based on quantitative data sources provided by different institutions: International Organization of Vine and Wine (OIV), Brazilian Union of Viticulture (UVIBRA), Ministry of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
0
4
0
1
Order By: Relevance
“…2). In a study made by Wurz et al [8], it was observed that in Brazil the sparkling wines are the most promising wine-growing product, with the greatest potential to increase its commercialization, both in the domestic and abroad markets, especially Muscat sparkling wines.…”
Section: Resultsmentioning
confidence: 99%
“…2). In a study made by Wurz et al [8], it was observed that in Brazil the sparkling wines are the most promising wine-growing product, with the greatest potential to increase its commercialization, both in the domestic and abroad markets, especially Muscat sparkling wines.…”
Section: Resultsmentioning
confidence: 99%
“…Both products have different origin, such as cider, since the XX century, that can be considered recent in the Brazilian market [31]. The sparkling wine moscatel is also new on the Brazilian market [6], that could explain the differences between the inductors.…”
Section: Discussionmentioning
confidence: 99%
“…In other cases, non-traditional products have also gained market importance. This is the case of sparkling wine "moscatel" in Brazil [5,6] and "Crémants" in France, which are more accessible wine accessible [7].…”
Section: Introductionmentioning
confidence: 99%
“…[12] show that in the last 10 years there has been a 280% increase in the production of sparkling wines, 80% of which is for domestic consumption in the country. [13] suggest that this increase of production and consumption is a consequence of the increase of the quality and typicality of the products.…”
Section: Introductionmentioning
confidence: 99%